Penyuluhan dan Penyediaan Sekat Belajar dalam Rangka Pencegahan Covid-19 Saat Tatap Muka di SMK N 17 Samarinda - Kusumawati, Rindha Mareta; Suwignyo, Suwignyo; Apriyani, Apriyani; Wulandari, Kartina (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2022)
The implementation of the new normal during the Covid-19 pandemic is affecting education systems around the world. The application of learning from home is mandatory in all regions in Indonesia. The disadvantages of learning from home are the lack of comprehensive teaching materials and the lack of supporting facilities when studying from home. For this reason, the local government, especially in Samarinda City, proposes face-to-face meetings in early 2022 starting at high school. However, this requires the provision of supporting facilities in the context of preventing COVID-19 in schools. The service team carried out a movement to provide supporting facilities needed by the school, namely the learning divider at SMK N 17 Samarinda. This provision uses a partition made of mica so as not to block the students' view while in class. And it is hoped that it can support students to carry out face-to-face learning with an offline system and prevent the risk of transmission through droplets while in class.Pemberlakuan new normal selama pandemic Covid-19 mempengaruhi system pendidikandi seluruh dunia. Penerapan belajar dari rumah menjadi hal wajib di seluruh daerah di Indonesia. Kekurangan belajar dari rumah adalah tidak tersampaikannya materi ajar secara menyeluruh dan kurangnya fasilitas pendukung saat belajar dari rumah. Untuk itu pemerintah daerah khususnya di Kota Samarinda mengusulkan tatap muka pada awal tahun 2022 di mulai pada sekolah menengah atas. Namun hal ini memerlukan pengadaan fasilitas pendukung dalam rangka pencegahan covid-19 di sekolah. Tim pengabdian melakukan suatu gerakan pemberian fasilitas pendukung yang diperlukan pihak sekolah yaitu sekat belajar di SMK N 17 Samarinda. Penyediaan ini menggunakan partisi berbahan mika agar tidak menghalangi pandangan siswa/I saat berada dikelas. Dan diharapkan dapat mendukung siswa/I untuk pelaksanaan pembelajaran tatap muka dengan system luring (offline) dan mencegah resiko penularan melalui droplet saat di kelas.